Beyond hydrophobicity: how F4-TCNQ doping of the hole transport material improves stability of mesoporous triple-cation perovskite solar cells - Liu Maning; Dahlstrom Staffan; Ahlang Christian; Wilken Sebastian; Degterev Aleksandr; Matuhina Anastasia; Hadadian Mahboubeh; Markkanen Magnus; Aitola Kerttu; Kamppinen Aleksi; Deska Jan; Mangs Oliver; et al. (ROYAL SOC CHEMISTRY, 2022)
Despite the outstanding power conversion efficiency of triple-cation perovskite solar cells (PSCs), their low long-term stability in the air is still a major bottleneck for practical applications. The hygroscopic dopants traditionally used in hole transport materials (HTMs) severely degrade the perovskite film. The p-type F4-TCNQ doping of the well-known spiro-OMeTAD HTM enables hydrophobicity-induced protection of the perovskite layer underneath. Nevertheless, the mechanism of F4-TCNQ doping in stabilizing PSCs is still rather unclear. Herein, when F4-TCNQ was adopted as the sole dopant of spiro-OMeTAD, highly stable mesoporous triple-cation PSCs were developed, with a very long T80 lifetime of more than 1 year (∼380 days) for devices stored in air (RH ∼ 40%). The present comprehensive experimental and theoretical studies on F4-TCNQ-doped spiro-OMeTAD reveal that the hydrophobic protection of the perovskite layer underneath is not the only reason for the increased long-term stability of the devices. The high uniformity of F4-TCNQ doping in the spiro-OMeTAD layer and less dopant aggregation and dopant migration towards the anode are key factors responsible for the increased stability of the perovskite solar cells when compared to conventional hygroscopic dopants. This work paves the way for future doping engineering of HTMs for PSCs with competitive stability.